Relevansi Pemikiran Legal Protection for Girl Victims of Sexual Violence Based on Trauma-Informed Justice - Rizky Ayu; Beni Arbi Batubara; Idar Sri Afriyanti Zebua (Jurnal Penelitian Medan Agama, 2026)
Sexual violence against girls is a serious violation of human rights that creates long-term physical, psychological, social, and legal consequences. In criminal justice practice, child victims may experience revictimization when investigation, prosecution, and trial procedures do not adequately consider their traumatic conditions. This study aims to analyze legal protection for girl victims of sexual violence based on Trauma-Informed Justice and to identify implementation gaps within the Indonesian criminal justice system. This research uses normative legal research with statutory, conceptual, and case approaches. Legal materials were collected through library research on legislation, official policy documents, international guidelines, and relevant scholarly literature. The findings show that Indonesia has strengthened victim protection through Law Number 12 of 2022 on Sexual Violence Crimes, Law Number 35 of 2014 on Child Protection, Law Number 11 of 2012 on the Juvenile Criminal Justice System, Law Number 3 of 2026 on Witness and Victim Protection, Government Regulation Number 30 of 2025, and related regulations. Nevertheless, implementation remains constrained by repeated questioning, limited trauma-informed facilities, uneven availability of psychologists and trained companions, and weak coordination among institutions. Therefore, trauma-informed legal protection requires child-friendly examination rooms, multidisciplinary assistance, confidentiality, prevention of direct confrontation with perpetrators, and comprehensive recovery services. Trauma-Informed Justice is essential to ensure that legal proceedings punish offenders while also protecting the dignity, safety, participation, and recovery of girl victims.